BRCA mutation screening and patterns among high-risk Lebanese subjects - Farra, Chantal; Dagher, Christelle; Badra, Rebecca; Hammoud, Miza Salim; Alameddine, Raafat; Awwad, Johnny; Seoud, Muhieddine; Abbas, Jaber; Boulos, Fouad; El Saghir, Nagi; Mukherji, Deborah (Hereditary cancer in clinical practice, 2019)
Background Previous studies have suggested that the prevalence of BRCA1 and 2 mutations in the Lebanese population is low despite the observation that the median age of breast cancer diagnosis is significantly lower than European and North American populations. We aimed at reviewing the rates and patterns of BRCA1/2 mutations found in individuals referred to the medical genetics unit at the American University of Beirut. We also evaluated the performance of clinical prediction tools. Methods We retrospectively reviewed the cases of all individuals undergoing BRCA mutation testing from April 2011 to May 2016. To put our findings in to context, we conducted a literature review of the most recently published data from the region. Results Two-hundred eighty one individuals were referred for testing. The prevalence of mutated BRCA1 or 2 genes were 6 and 1.4% respectively. Three mutations accounted for 54% of the pathogenic mutations found. The BRCA1 c.131G > T mutation was found among 5/17 (29%) unrelated subjects with BRCA1 mutation and is unique to the Lebanese and Palestinian populations. For patients tested between 2014 and 2016, all patients positive for mutations fit the NCCN guidelines for BRCA mutation screening. The Manchester Score failed to predict pathogenic mutations. Conclusion The BRCA1 c.131G > T mutation can be considered a founder mutation in the Lebanese population detected among 5/17 (29%) of individuals diagnosed with a mutation in BRCA1 and among 7/269 families in this cohort. On review of recently published data regarding the landscape of BRCA mutations in the Middle East and North Africa, each region appears to have a unique spectrum of mutations.